A Case of Paradoxical Embolism Causing Anterior Spinal Cord Syndrome and Acute Myocardial Infarction Following the Intradiscal Oxygen-Ozone Therapy - He, Runcheng; Huang, Qing; Yan, Xinxiang; Liu, Yunhai; Yang, Jie; Chen, Xiaobin (Frontiers in Neurology, 2019)
We report the case of a 66-year-old female who burst into flaccid paralysis of the lower extremities, accompanied by sensory losses associated with pain and temperature below T4, and bladder and rectal disturbances, during an oxygen–ozone injection for disc herniation. Half an hour, she suffered from chest pain. Magnetic resonance imaging (MRI) showed a hyperintense area in the thoracic spinal cord from T2 to T10 in sagittal T2-weighted images (T2WI). The electrocardiogram (ECG) had shown ST-segment elevation in V1-V6 leads. She was diagnosed with spinal cord infarction and ST-elevation myocardial infarction (STEMI). Transthoracic echocardiography showed the existence of a large patent foramen ovale (PFO) correlated with the detection of massive microbubbles in the left atrium. We discuss the potential role of paradoxical embolism through PFO as a possible mechanism of spinal cord infarction and myocardial infarction after intradiscal oxygen–ozone therapy.